Inundaciones en viviendas por lluvias y su relación con infecciones respiratorias agudas en menores de cinco años, Puerto Masusa 2025 - Ramirez Vasquez, Victor Hugo (2025)
The research project presented aims to determine whether flooding in homes caused by rainfall increases cases of acute respiratory infections in children under five years of age, using information from IPRESS I-4 Bellavista Nanay and Civil Defense in Puerto Masusa during 2025. The methodology is based on a quantitative approach with a non-experimental, correlational, and retrospective design, applied to a sample of 100 households through non probability convenience sampling. Data collection instruments include a questionnaire on flooding and an acute respiratory infection registration form, administered through surveys and document review. Data processing is conducted using the statistical software SPSS version 27.0, and the analysis is carried out using descriptive and inferential statistics, specifically the Chi Square test (X²), to assess the relationship between the variables and test the proposed hypothesis.